Pengendalian Internal Persediaan Obat-Obatan Pada Instalasi Farmasi Rumah Sakit Umum Daerah Kota Dumai - Muhammad Amrin Hakim; Rosmida Rosmida (Jurnal IAKP: Jurnal Inovasi Akuntansi Keuangan & Perpajakan, 2022)
This study aims to find out how the implementation of internal inventory control in the medicine (pharmaceutical) section of the Dumai City General Hospital which is located on Jalan Tanjung Jati No 4. Dumai City Regional General Hospital. This study uses descriptive analysis of the results of interviews with specified sources, field observations and documentation. Primary data were obtained from interviews and direct observations. While secondary data from documents related to drug supplies such as invoices, purchase invoices, receipt documents, inventory cards, expenditure documents, organizational structures, and letters of order. The results of this study indicate that the internal control of the supply of medicines is quite good and has not entered the very good category because there are several things that must be improved, namely the separation of duties that are listed in detail and there are still not carrying out according to procedures and the existence of arrears in payments to pharmaceutical companies and communication between related parties must be improved and improvements are still needed such as the addition of security devices and the area where the warehouse must be enlarged.